Just in Time Factory Implementation Through Lean Manufacturing Tools - Pinto, José Luís Quesado (Management for Professionals, 2018)
This book explains the implementation of just in time (JIT) production in an industrial context, while also highlighting the application of various, vital lean production tools. Shifting the trade-off between productivity and quality, the book discusses the preparation stages needed before implementing a JIT system. After an introduction to lean manufacturing and JIT, it introduces readers to the fundamentals and practice of Kaizen, paying special attention to lean manufacturing tools. The book demonstrates how to use the 5S approach (with the stages of Seiri, Seiton, Seiso, Seiketsu and Shitsuke), Standardized Work, Single Minute Exchange of Die (SMED) and the Kanban system. In brief, the book provides an understanding of the processes associated with the application of these tools and highlights the benefits attained by companies that have implemented JIT systems. Throughout the book, a real-world case study is used to deepen readers' understanding of how lean manufacturing tools can be implemented.The book is ideally suited for executive courses in industrial engineering and management, but can also be used for upper undergraduate and graduate courses at universities.